Genetic Variations and Frequencies of the Two Functional Single Nucleotide Polymorphisms of SLCO1B1 in the Thai Population - Chalitpon Na nakorn; Chalitpon Na nakorn; Chalitpon Na nakorn; Jariya Waisayarat; Charungthai Dejthevaporn; Pornpen Srisawasdi; Sansanee Wongwaisayawan; Chonlaphat Sukasem; Chonlaphat Sukasem (Frontiers Media S.A., 2020)
AimTo investigate the variations and the frequencies of the SLCO1B1 gene in the Thai population.MethodsCollected samples were categorized into five regions of Thailand. DNA samples were genotyped for two variants, c.388A>G and c.521T>C of the SLCO1B1, using TaqMan® real-time PCR.ResultsThe minor allele frequencies (MAFs) of two single nucleotide polymorphisms (SNPs) were not significantly different among the five regions. The most frequent haplotype was SLCO1B1*1b (frequency: 0.654), followed by *1a (frequency: 0.217), *15 (frequency: 0.128), and *5 (frequency: 0.001). We observed a similar frequency of OATP1B1 transporter phenotypes compared to other populations. 75.85% of the Thai subjects showed normal OATP1B1 activity, 22.5% showed intermediate OATP1B1 activity, and 1.58% showed low OATP1B1 activity.ConclusionThis study reported the frequencies of the SLCO1B1 variants and the subsequent OATP1B1 activity in a large cohort of Thais that can provide important information for the guidance of personalized drug therapy.